The triazine herbicides : 50 years revolutionizing agriculture - LeBaron, Homer M.; McFarland, Janis E., 1956-; Burnside, Orvin; ScienceDirect eBooks (Amsterdam ; London : Elsevier, 2008)
Over the past 50 years, triazines have made a great impact on agriculture and world hunger by assisting in the development of new farming methods, providing greater farming and land use capabilities, and increasing crop yields. Triazines are registered in over 80 countries and save billions of dollars a year. The Triazine Herbicides is the one book that presents a comprehensive view of the total science and agriculture of these chemicals. With emphasis on how the chemicals are studied and developed, reviewed, and used at the agricultural level this book provides valuable insight into the benefits of triazine herbicides for sustainable agriculture. * Presents previously unpublished information on the discovery, development and marketing of herbicides * Includes a vital section on the origin, use, economics and fate of triazine herbicides * Covers benefits of triazines in corn and sorghum, sugarcane, citrus, fruit and nut crops * Establishes best management practice and environmental benefits of use in conservation tillage.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Herbicides; Triazines; TECHNOLOGY & ENGINEERING -- Pest Control; Herbicides; Triazines; Herbizid; Triazine; Electronic books